HOW WE FAILED TO PLAN FOR HABITABILITY - Lik Meng, Lee; Abdullah, Aldrin; Sook Fern, Tan; Badarulzaman, Nurwati; Hassan, Ahmad Sanusi (PLANNING MALAYSIA, 2006)
A quality housing development should not only take into account the physical aspects of design but also be sensitive to human needs. Habitability in housing involves several components, including environmental factors, man-made designs, socio-cultural operations and psychological impacts. Elements of habitability can be observed in various concepts of residential developments including classical concepts such as the Garden City Movement and the Neighbourhood Unit. In Malaysia, the Malay Kampung and the Chinese New Village exemplify some ideal living practices relating to habitability. Both the classical and traditional concepts influenced subsequent residential developments in Malaysia such as the Jengka Project, Kampung Tersusun, Town 8, Cyberjaya and Putrajaya. However, not all residential developments succeeded in creating a quality living environment. More recent concepts such as the New Urbanism and the China Healthy Residence have placed greater emphasis in dealing with such issues. In Malaysia, legislations and policies have not adequately addressed the problems on habitability. We lack a thorough planning system, which prepares and monitors the quality of our residential development. Failures in planning policies have also created other planning issues that affect habitability, as portrayed in the case of the Rifle Range Low-cost Flats in Penang. The top-down approach in housing policy and planning should be geared up to match the growth of community towards achieving habitability.